Literature Review Pengaturan Tekanan Darah Dengan Low Impact Exercise Pada Penderita Hipertensi Di Masa Pandemi COVID-19 - Widia, Chita; Kurniasih, Eli; Alifiar, Ilham (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Â To examine articles related to research on the effectiveness of low impact exercise on cardiovascular and to examine articles related to research on the effectiveness of low impact exercise to lowering blood pressure in patients with hypertension. Methods: This article uses t theÂ literature review method. The population of articles used in this KTI is all articles on Google Scholar, ProQuest, and Science Direct both in Indonesian and English. The number of samples is 11 articles with research titles on the effectiveness of low impact exercise therapy on blood pressure in patients with hypertension with the type of empirical research published in the last five yearsResults: From the overall results of the study, it was found that low-impact exercise was effective in reducing blood pressure in patients with hypertension.Conclusion: Low impact exercise regularly in 4-12 weeks in 20-30 minutes every exercise can reduce high blood pressure effectively.